2007
DOI: 10.3168/jds.2007-0287
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Continuous Lactation and Increased Milking Frequency on Milk Production and Mammary Cell Turnover in Primiparous Holstein Cows

Abstract: We hypothesized that early-lactation increased milking frequency, in combination with bovine somatotropin (bST), would improve milk yield in continuously milked (CM) primiparous glands through greater mammary epithelial cell (MEC) function, proliferation, and reduced apoptosis (cell turnover). Primiparous cows were randomly assigned to a 2 x 2 x 2 factorial with a split-plot design to either a continuous bST (+bST, n = 4) or no bST (-bST, n = 4) treatment throughout the study. Within each animal, udder halves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…The use of rbST both prepartum and postpartum in multiparous cows has been successful in both short dry period (Bachman 2002;Annen et al, 2004a;Gulay et al, 2004) and CM studies (Annen et al, 2004a), but has not been successful in studies using primiparous cows (Annen et al, 2004a andFitzgerald et al, 2007). A more recent study (Klusmeyer et al, 2009) was not able to repeat the findings of Annen et al (2004a) in rbST-supplemented CM multiparous cows.…”
Section: Collier Annen-dawson and Pezeshkimentioning
confidence: 99%
See 2 more Smart Citations
“…The use of rbST both prepartum and postpartum in multiparous cows has been successful in both short dry period (Bachman 2002;Annen et al, 2004a;Gulay et al, 2004) and CM studies (Annen et al, 2004a), but has not been successful in studies using primiparous cows (Annen et al, 2004a andFitzgerald et al, 2007). A more recent study (Klusmeyer et al, 2009) was not able to repeat the findings of Annen et al (2004a) in rbST-supplemented CM multiparous cows.…”
Section: Collier Annen-dawson and Pezeshkimentioning
confidence: 99%
“…Although some studies have reported that omitting the dry period did not have an impact on the milk production of the next lactation either without using bovine rbST in dairy cows (Remond and Bonnefoy, 1997) or using bovine somatotropin (bST) in multiparous cows (Annen et al, 2004a), in most studies it has resulted in production losses of 10% to 40% in the subsequent lactation (Andersen et al, 2005;Fitzgerald et al, 2007).…”
Section: Impact On Milk Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…A high protein value of the milk contributes to a more stable metabolic status of the cow, grades up the delivered milk, and has got a particularly high biological value and nutrient concentration (Lee and Lorenz, 1978;Haug et al, 2007). In search of ways to increase the protein concentration of the milk, and to conserve the metabolism of the cow at the same time, the research regarding the neglecting of the dry period is of major interest (Remond et al, 1992;Remond and Bonnefoy, 1997;Remond et al, 1997a and1997b;Andersen et al, 2005;Fitzgerald et al, 2007;Madsen et al, 2008). The drying-off period is regarded to be the recreational period for the udder: cellular regeneration takes place and the preconditions for a high milk output in the following lactation are set.…”
Section: Introductionmentioning
confidence: 99%
“…Diet has a profound effect on de novo fatty acid synthesis in the mammary gland, brown and white adipose tissues as well as the liver [1,2,3,4]. In these cases, the rate of fatty acid synthesis is significantly altered by the amount of carbohydrate or fat present in the diet [5][6].…”
Section: Introductionmentioning
confidence: 99%